Climate change in Argentina: trends, projections, impacts and adaptation. (3rd November 2014) - Barros, Vicente Ricardo; Boninsegna, José Armando; Camilloni, Inés Angela; Chidiak, Martina; Magrín, Graciela Odilia; Rusticucci, Matilde
<x xml:space="preserve">Abstract</x> In most of Argentina, the warming since 1901 was a little lower than the global average, although with strong trends in temperature extremes and in heat waves during the most recent decades. There was a remarkable increase in precipitation over most of subtropical Argentina, especially since 1960. This has favored agriculture yields and the extension of crop lands into semiarid regions, but this increase also came with more frequent heavy rainfalls and consequent flooding of rural and urban areas. Since the early 1970s, the main rivers of the Plata Basin have increased their mean flows, but this was attributable not only to increased precipitation, but also to land use changes. In contrast, over the Andes Mountains, reduced rainfall and increased temperature has led to glaciers receding and reduced river flows. Climate projections for the first half of this century maintain observed trends and raise additional concerns that in most cases can be dealt with timely adaptation policies. However, by the end of this century, under an extreme emissions scenario, the projected warming reaches 3.5°C in the north of the country with respect to present‐day conditions. There is insufficient knowledge to assume that this warming would not create severe damages to the people and the economy of Argentina. Because of the damages and casualties that heat waves and extreme precipitation events are already producing, the first and most urgent adaptation required is to reinforce early warning systems and contingency planning to cope with climatic extremes and their consequences on health. WIREs Clim Change 2015, 6:151–169. doi: 10.1002/wcc.316 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.